Essays in financial crises - Zheng, Huanhuan (2011)
This thesis explores the power of deterministic dynamic model in capturing the qualitative attributes of financial crises and statistical features of the financial time series. It is shown that, even without any random processes/variables, the deterministic dynamic model performs well in generating crises of different patterns which are distinguished by their durations and accumulative depth and in reproducing a wide range of stylized facts that are common across financial markets. Such good performance is ascribed to the innovative modeling of investors' beliefs. Specifically, investors' beliefs are regime-dependent, they are updated according to various psychological trading regimes enclosed by different support and resistance prices.